A summary of the Malaysian Clinical Practice Guidelines on the management of postmenopausal osteoporosis, 2022 - Terence Ing Wei Ong; Lee Ling Lim; Siew Pheng Chan; Winnie Siew Swee Chee; Alan Swee Hock Ch’ng; Elizabeth Gar Mit Chong; Premitha Damodaran; Fen Lee Hew; Luqman bin Ibrahim; Hui Min Khor; Pauline Siew Mei Lai; Joon Kiong Lee; et al. (Osteoporosis and Sarcopenia, 2023)
Objectives: The aim of these Clinical Practice Guidelines is to provide evidence-based recommendations to assist healthcare providers in the screening, diagnosis and management of patients with postmenopausal osteoporosis (OP). Methods: A list of key clinical questions on the assessment, diagnosis and treatment of OP was formulated. A literature search using the PubMed, Medline, Cochrane Databases of Systematic Reviews, and OVID electronic databases identified all relevant articles on OP based on the key clinical questions, from 2014 onwards, to update from the 2015 edition. The articles were graded using the SIGN50 format. For each statement, studies with the highest level of evidence were used to frame the recommendation. Results: This article summarizes the diagnostic and treatment pathways for postmenopausal OP. Risk stratification of patients with OP encompasses clinical risk factors, bone mineral density measurements and FRAX risk estimates. Non-pharmacological measures including adequate calcium and vitamin D, regular exercise and falls prevention are recommended. Pharmacological measures depend on patients’ fracture risk status. Very high-risk individuals are recommended for treatment with an anabolic agent, if available, followed by an anti-resorptive agent. Alternatively, parenteral anti-resorptive agents can be used. High-risk individuals should be treated with anti-resorptive agents. In low-risk individuals, menopausal hormone replacement or selective estrogen receptor modulators can be used, if indicated. Patients should be assessed regularly to monitor treatment response and treatment adjusted, as appropriate. Conclusions: The pathways for the management of postmenopausal OP in Malaysia have been updated. Incorporation of fracture risk stratification can guide appropriate treatment.